The ROAR Internship Program: Paid employment as a strategy for engagement - Phillips, Kristina (Experiential Learning and Teaching in Higher Education, 2024)
The ROAR program at Jackson State University is an integrated strategy for Re-envisioning Orientation, Advising and Retention. Continuing JSU students apply for paid internships in which they co-design the next cohort’s First-Year Experience. During the academic year they lead brainstorming sessions, develop detailed programming, and pitch to faculty – developing deeper connections to the university as well as transferable workforce skills.